Debt equity swaps and financial development in the Caribbean - Boamah, Daniel (Caribbean Centre for Monetary Studies [St. Augustine]TT, 1996)
Discusses the principles involved in debt swaps, concentrating on their economic implications and on how such implications have influenced specific country programmes. Discusses the possible application of the principles to regional and national debt issues.